Narrating the Consequences of Conflict: Death, Survival and the ‘Autobiographical Turn’ in the Criminology of War - Hearty, Kevin (The British journal of criminology, 2025)
Locating itself within narrative criminological scholarship and the criminology of war literature, this article critically examines how the themes of death and survival are understood and represented in the memoirs of former Irish Republican Army (IRA) members. Building on the recent ‘autobiographical turn’ in the criminology of war, it identifies how death is storied from perspectives that reflect the nature of armed conflict, capture human loss, and criticize the leadership. Similarly, it shows how survival is storied as having outlived the conflict, living a meaningful post-conflict life, and addressing the legacy of conflict. It is concluded that these memoirs are a valuable dataset that amplify counter-discourses based on the lived experience of former combatants from non-state armed groups.